Entrepreneurship in the global firm - Birkinshaw, Julian M. (Sage strategy series., 2000)
"Based on fresh case evidence, the findings presented in Entrepreneurship in the Global Firm will have an impact on some of the key debates on the transfer of knowledge in firms, the resource-based view and the network forms of organization." "The author concentrates on the initiatives of subsidiary managers and then broadens out into an analysis of how subsidiary companies evolve over time, and how they are able to drive changes in the global firm as a whole. By taking the perspective of the subsidiary manager operating in a network, Birkinshaw extends the implications of his findings to all managers in organizations and challenges those who still view organizations as hierarchies." "The data and arguments presented here offer essential material to advanced undergraduate, MBA and postgraduate students of organizational forms, corporate strategy and the multinational enterprise."--Jacket